Excited states of protonated DNA/RNA bases - Berdakin, Matias (2014)
The very fast relaxation of the excited states to the ground state in DNA/RNA bases is a necessary process to ensure the photostability of DNA and its rate is highly sensitive to the tautomeric form of the bases. Protonation of the bases plays a crucial role in many biochemical and mutagenic processes and it can result in alternative tautomeric structures, thus making important the knowledge of the properties of protonated DNA/RNA bases. We report here the photofragmentation spectra of the five protonated DNA/RNA bases. In most of the cases, the spectra exhibit well resolved vibrational structures, with broad bands associated with very short excited state lifetimes. The similarity between the electronic properties, e.g. excitation energy and very short excited state lifetimes for the canonical tautomers of protonated and neutral DNA bases, suggests that the former could also play an important role in the photostability mechanism of DNA.